Stream of Education and its Impact on Stress: The Influence of Field of Study on Stress Levels among Post-Graduate Students (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In today's world life is full of hassles, demands, competitions, expectations, and frustrations. An individual can be safe only when heshe can recognizing the cues and symptoms of stress and taking necessary actions to reduce its effects which are indeed very harmful. There is a gush of hormones adrenaline and cortisol which are released when a person perceives threat. The aim of the present study was to compare the students stress among the post graduate students of Physical Education, Sociology, Performing Arts and Women Studies of Bangalore University, the study sample consisted of 126 students pursuing their masters, out of which 29, 37, 30 and 30 students respectively, were administered the same questionnaire. To find out the difference in stress One Way ANOVA was applied. It was found that no significant difference existed among the Post Graduate students of the four departments of Bangalore University, this shows that the field of study does not have an influence on the stress level of students. Factors that are common across departments such as group work, interaction, and that these students are regular students who attend class with not much responsibility of running a family or working for their daily necessities, could be reasons why the stress levels do not show any significant difference.